2007
DOI: 10.1292/jvms.69.1081
|View full text |Cite
|
Sign up to set email alerts
|

Ceftiofur Distribution in Plasma and Tissues Following Subcutaneously Administration in Ducks

Abstract: ABSTRACT. A study was performed to determine the residues in blood and edible tissues of healthy ducks (25 days old, mean body weight 1.0 ± 0.13 kg) after subcutaneous administration of ceftiofur sodium at a dose rate of 2 mg/kg body weight (Group I) and 4 mg/kg body weight (Group II). Blood, muscle, liver, kidney, and fat samples were collected from all of ducks on the 1st, 2nd, 3rd, 4th, and 5th day after treatment of drug, and ceftiofur was analyzed with a high-performance liquid chromatography (HPLC) assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
2
5
0
Order By: Relevance
“…These results are slightly agreed with that reported by El-Sayed et al [11] who mentioned that kidney and liver have the highest drug concentrations, while the lowest was in thigh muscle at the 1 st day after stoppage of intramuscular administration of ceftiofur at a dose of 10 mg/kg BW for 5 days. Also, our results are in agreement with Chung et al, [6] who stated that kidney contained the highest drug residue concentration. Also, they reported that the drug residue concentration in muscle (0.071±0.01 μg/g) was more than in liver (0.066±0.01 μg/g) at the 1 st day post-drug medication (4 mg/kg BW subcutaneously for 1 day) which was disagreed with our result.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results are slightly agreed with that reported by El-Sayed et al [11] who mentioned that kidney and liver have the highest drug concentrations, while the lowest was in thigh muscle at the 1 st day after stoppage of intramuscular administration of ceftiofur at a dose of 10 mg/kg BW for 5 days. Also, our results are in agreement with Chung et al, [6] who stated that kidney contained the highest drug residue concentration. Also, they reported that the drug residue concentration in muscle (0.071±0.01 μg/g) was more than in liver (0.066±0.01 μg/g) at the 1 st day post-drug medication (4 mg/kg BW subcutaneously for 1 day) which was disagreed with our result.…”
Section: Discussionsupporting
confidence: 93%
“…Extraction was carried out according to Chung et al [6]. Frozen samples were thawed at room temperature (23°C).…”
Section: Analytical Proceduresmentioning
confidence: 99%
“…Levels in the thigh muscle were lower, whereas the highest concentrations were detected in the kidneys. This is in agreement with previous findings after intramuscular treatment of swine Beconi-Barker et al 1997) and subcutaneous injection of ducks (Chung et al 2007). It is concluded that, from an analytical point of view, poultry kidney is potentially better suited for detecting off-label use of ceftiofur.…”
Section: Application To Other Matricessupporting
confidence: 92%
“…The pharmacokinetics profiles of ceftiofur have been determined in different avian species, such as chickens (Tell et al, 1998), ducks (Chung et al, 2007;Hope et al, 2012), geese (Chen et al, 2014) and turkeys (Tell et al, 1998). Ceftiofur has some similar pharmacokinetics profiles in these birds, such as a relatively poor distribution, but a quick and complete transformation to its active metabolites, desfuroylceftiofur (DCE) and desfuroylceftiofur conjugates (DCEC).…”
Section: Introductionmentioning
confidence: 99%